2021
DOI: 10.1186/s12888-021-03522-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring low grade inflammation by soluble urokinase plasminogen activator receptor levels in schizophrenia: a sex-dependent association with depressive symptoms

Abstract: Background There is evidence of increased low grade inflammation (LGI) in schizophrenia patients. However, the inter-individual variation is large and the association with demographic, somatic and psychiatric factors remains unclear. Our aim was to explore whether levels of the novel LGI marker soluble urokinase plasminogen activator receptor (suPAR) were associated with clinical factors in schizophrenia and if such associations were sex-dependent. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Previous studies had shown that pathways include neutrophil degranulation [74], immune system [75], extracellular matrix organization [76], toll-like receptor cascades [77], cytokine signaling in immune system [78], metabolism of RNA [79] and gene expression [80] were involved in the progression of CF. NTRK3 [81], MMP9 [82], IGF2 [83], SOCS3 [84], IGFBP2 [85], SLC1A3 [86], NOS1AP [87], HP (haptoglobin) [88], TLR5 [89], ARG1 [90], NRG1 [91], RGS5 [92], LCN2 [93], TSPO (translocator protein) [94], PLAU (plasminogen activator, urokinase) [95], MME (membrane metalloendopeptidase) [96], BST1 [97], NR6A1 [98], TLR4 [99], NRN1 [100], ABCA13 [101], CTSD (cathepsin D) [102], NCAM1 [103], SIGMAR1 [104], CNR2 [105], CCR4 [106], ABCB1 [107], TIMELESS (timeless circadian regulator) [108], IRF8 [109], TXNIP (thioredoxin interacting protein) [110], SUV39H1 [111], CRY1 [112], CRY2 [113], PDCD4 [114] and MGAT5 [115] played an important role in depression and anxiety. Accumulating evidence has demonstrated that MMP9 [116], S100A12 [117], HP (haptoglobin) [118], TLR5 [119], NRG1 [120], PLAU (plasminogen activator, urokinase) [121], SLC11A1 [122], AQP9 [123], CHIT1 [124], TLR4 [125], SLC26A8 [126], CTSD (cathepsin D) [127], SERPINB1 [128], FASLG (Fas ligand) [129], SLC4A4 [130], AQP3 [131] and IRF8 [132] appears to be constitutively associated with CF .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that pathways include neutrophil degranulation [74], immune system [75], extracellular matrix organization [76], toll-like receptor cascades [77], cytokine signaling in immune system [78], metabolism of RNA [79] and gene expression [80] were involved in the progression of CF. NTRK3 [81], MMP9 [82], IGF2 [83], SOCS3 [84], IGFBP2 [85], SLC1A3 [86], NOS1AP [87], HP (haptoglobin) [88], TLR5 [89], ARG1 [90], NRG1 [91], RGS5 [92], LCN2 [93], TSPO (translocator protein) [94], PLAU (plasminogen activator, urokinase) [95], MME (membrane metalloendopeptidase) [96], BST1 [97], NR6A1 [98], TLR4 [99], NRN1 [100], ABCA13 [101], CTSD (cathepsin D) [102], NCAM1 [103], SIGMAR1 [104], CNR2 [105], CCR4 [106], ABCB1 [107], TIMELESS (timeless circadian regulator) [108], IRF8 [109], TXNIP (thioredoxin interacting protein) [110], SUV39H1 [111], CRY1 [112], CRY2 [113], PDCD4 [114] and MGAT5 [115] played an important role in depression and anxiety. Accumulating evidence has demonstrated that MMP9 [116], S100A12 [117], HP (haptoglobin) [118], TLR5 [119], NRG1 [120], PLAU (plasminogen activator, urokinase) [121], SLC11A1 [122], AQP9 [123], CHIT1 [124], TLR4 [125], SLC26A8 [126], CTSD (cathepsin D) [127], SERPINB1 [128], FASLG (Fas ligand) [129], SLC4A4 [130], AQP3 [131] and IRF8 [132] appears to be constitutively associated with CF .…”
Section: Discussionmentioning
confidence: 99%
“…The current study is a part of the Effect of Physical Activity on Psychosis Study (EPHAPS), approved by the Regional Committees for Medical and Health Research Ethics (trial number 2014/372), and is examining LGI and factors influencing LGI in a physical exercise intervention RCT with observer-blinded parallel group design ( 33 ). The current sample has been studied as a part of a larger cross-sectional sample ( 6 , 16 ), and in an RCT setting with a physical exercise intervention investigating effect on CRF, cognition and symptoms ( 34 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation is considered a cause of non-communicable diseases, such as cardiovascular disease (CVD) and type II diabetes, and is associated with schizophrenia, depression, reduced quality of life and reduced motivation (4,(6)(7)(8)(9). Thus, inflammation may represent a possible link between schizophrenia and increased risk of somatic and psychiatric comorbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual relationships of these markers with various mental disorders in perinatal and offspring outcomes, chronic states, and pre/post-treatment have been examined based on cytokines, C-reactive protein, hormones, neurotrophins, and so on. Some commonly investigated cytokine measures are summarized in Table 1 [ 12 , 40 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. When interpreting reports of individual studies, it is crucial to consider the extent to which other factors affecting peripheral cytokines are accounted for in specific analyses.…”
Section: Potential Inflammatory Biomarkers In Adhdmentioning
confidence: 99%